Molecular Characterization, Spatial–Temporal Expression Profiles, and Injury‐responsive Regulation of Myocyte‐specific Enhancer Factor 2 Gene Family in the Ricefield Eel, Monopterus albus. Issue 2 (1st February 2018) - Wu, Ping; Chen, Dunxue; Cheng, Jia; Chen, Lin; Chu, Wuying; Zhang, Jianshe; Liu, Li; Zeng, Guoqing
Abstract: The myocyte‐specific enhancer factor 2 (MEF2) gene family members are well‐established regulators in the control of muscle repair, regeneration, and development. In this study, we cloned the CDS sequences of the four MEF2 family members in the ricefield eel, and their coding sequences (CDS) lengths were 1449 bp, 1419 bp, 1431 bp, and 1608 bp, respectively. Sequence analysis demonstrated that three of them shared four conserved protein domains, including a MADS‐Box, inside SRF‐TF domains, adjacent conserved MEF2 domains, the HJURP‐C domains, while MEF2B have no HJURP‐C domains. Phylogenetic tree analyses indicated that the MEF2 family members were clustered together with those of fish species, and MEF2A, MEF2C, and MEF2D were closely clustered together and kept away from MEF2B. Spatial–temporal expression profiles displayed that the messenger RNA (mRNA) levels of MEF2 were upregulated with the developmental stage and were especially highly expressed significantly in skeletal muscles. After subcutaneous injection of bupivacaine hydrochloride, mRNA levels of MEF2 family and rapidly performed injury‐responsive regulation after damage that firstly increased, then decreased until normal levels were recovered, the same as the change in muscle fiber cells. In conclusion, the MEF2 gene family plays a central role in muscle repair, regeneration, and development in fish, at least in the ricefield eel.